FDI inflow analysis in oil and gas industry of the Republic of Uzbekistan - ABDUKADIROV, Azizbek (Graduate School of International Studies Ajou University, 2010)
Foreign direct investment (FDI) has become one of the vital factors for economic and social improvements of developing states. Because of FDI inflows we can observe new cash inflows to the national economy, new technology, additional work places for work force of a country etc. But is FDI effective? How does it affect industries? Should we protect our strategic industries from FDI? How can we allocate FDI in efficient way? To answer those questions I chose oil and gas industry as a field of observation. This industry is relatively new for Uzbekistan and during the last 6 years this industry has become the most attractive field for foreign investors. Or by the other hand oil and gas industry is a strategic complex in Uzbekistan and from the strategic point of view we might think that FDI participation is not necessary. Furthermore another important question arises when the main FDI inflows to exploration and producing of raw materials such as gas and condensate rather than production of goods which can increase the income to the budget of the state for 10 times. Taking into account above mentioned questions the main research area of my thesis will be: 1)Learn the past, present and future opportunities for foreign investors; 2)Compare attractive areas in oil and gas industry for FDI and find out more effective way of investing for both state and foreign investor; 3)Give my own suggestions concerning above mentioned questions. In order to achieve the goals above I will use also an econometric model which makes this work unique and doubtless of my results.
학위논문(석사)--아주대학교 국제대학원--국제경영학과,2010. 4